Integrating Wordwall Gamification Into Literacy Learning: Teacher and Student Perspectives - Aisyah Eka Alfina; Munirah Munirah; Syahruddin Syahruddin (International Journal Labs, 2026)
The background of this research stems from the need to present literacy learning that is more interactive, engaging, and oriented toward students’ active involvement. This study aims to analyze the integration of gamification through the use of the Wordwall application in literacy learning, as viewed from the perspectives of teachers and students. The research method employs a descriptive qualitative approach, involving teachers and secondary school students as the primary participants. Data were collected through in-depth interviews, observations, and documentation of learning activities using Wordwall as a learning medium. The results of the study show that the use of Wordwall-based gamification is able to increase learning motivation, student participation, and understanding of literacy materials. Teachers consider Wordwall to be a flexible, user-friendly, and effective medium for creating a collaborative learning environment. Meanwhile, students reported that game elements such as points, challenges, and rankings increase interest and foster healthy competition in the classroom. However, several obstacles were also identified, such as limited internet connectivity and the varying levels of digital literacy among some teachers. This research confirms that the integration of Wordwall into literacy learning functions not only as a technological innovation but also as a pedagogical strategy that supports active, contextual, and student-centered learning. These findings are expected to serve as a foundation for developing gamification-based learning models that are relevant to the demands of the digital era in schools.